Learning to Read the Yellow Book on @Nahwu_Pedia Instagram Account Reels - Ulhaq, Fazrina Dhiya; Saleh, Nalahuddin; Subandi, Aldy Saputra (STUDI ARAB, 2023)
The times are changing for better or worse. Instagram @Nahwu_Pedia makes a transition both in terms of content and utilization of the Reels feature. This transition can affect its effectiveness as a digital-based yellow book reading learning media. Research was conducted to review the effectiveness and relevance of Instagram @Nahwu_Pedia which underwent a transition. The research used descriptive qualitative with participants, namely researchers, account owners, and 17 old followers. The sample was taken using purposive sampling. Data collection techniques were observation, interview, questionnaire, and documentation. Data were analyzed by data reduction, data presentation, and conclusions. The findings show that Instagram @Nahwu_Pedia is effective and relevant to the fulfillment of the indicators of learning effectiveness according to Hamzah B. Uno, although there is a transition in content and features in the rapid development of the digitalization era.